THE EFFECT OF EDUCATION, PERCAPITA INCOME, AND UNEMPLOYMENT ON POVERTY (CASE STUDY KABUPATEN MALANG 2001-2016) - Hardityo Erik Sujatmiko (Jurnal Ilmiah Mahasiswa FEB, 2018)
Welfare is the purpose of the national development. To achieve national welfare, government should reduce poverty by developing education, increasing per capita income and razing unemployment. This study aims to to know the effect of education, per capita income and unemployment on the poverty in Malang district.The analysis used multiple linear method. The results of multiple linear regression found that the education variable has no significant effect on poverty. This indicates that a change in the level of education would not affect the level of poverty. The education variable takes a long period of time to take effect. The per capita income variable had a significant negative effect and the unemployment variable has a significant positive effect, meaning an increase in unemployment will increase the level of poverty.Key words : education, per capita income, unemployment, poverty